(E)-4-[4-(Diethylamino)benzylideneammonio]benzenesulfonate - Pumsak Ruanwas; Suchada Chantrapromma; Hoong-Kun Fun (Acta Crystallographica Section E, 2012)
The title compound, C17H20N2O3S, synthesised from sulfanilic acid and 4-diethylaminobenzaldehyde, crystallized out as a zwitterion with the central N atom protonated. The zwitterion exists in an E conformation with respect to the C=N double bond. The dihedral angle between the benzene rings is 37.57 (5)°. In the crystal, the zwitterions are linked into a tape along the a axis by N—H...O hydrogen bonds. The crystal structure is further stabilized by weak C—H...O interactions and π–π interactions with a centroid–centroid distance of 3.8541 (6) Å. An O...O [2.8498 (11) Å] short contact is present.